2005
DOI: 10.1002/ijc.21171
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E amides, a new class of vitamin E analogues with enhanced proapoptotic activity

Abstract: Vitamin E (VE) analogues, epitomized by a-tocopheryl succinate (a-TOS), are proapoptotic agents with selective antineoplastic activity. The molecule of a-TOS comprises several structurally and functionally distinct moieties that can be modified in order to yield analogues with higher activity. In order to find analogues with higher apoptogenic efficacy, we prepared novel compounds where the ester bond was replaced by an amide bond. All of these analogues were significantly more proapoptotic than their ester co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 36 publications
1
43
1
Order By: Relevance
“…This follows from our previous work, in which we showed that masking the free carboxylate of vitamin E analogues by methylation negated their ability to kill cancer cells (36,37). We tested whether lysosomal function was important for apoptosis induction by a-TOS-LTVSPWY due to presence of peptidases in the organelles.…”
Section: Resultsmentioning
confidence: 94%
“…This follows from our previous work, in which we showed that masking the free carboxylate of vitamin E analogues by methylation negated their ability to kill cancer cells (36,37). We tested whether lysosomal function was important for apoptosis induction by a-TOS-LTVSPWY due to presence of peptidases in the organelles.…”
Section: Resultsmentioning
confidence: 94%
“…When the ester bond is replaced by an amide bond, further enhancement of proapoptotic activity was observed (12, 13, 37, and 38) (Tomic-Vatic et al, 2005). Again, the unsaturated amides (13 and 38) were superior to their saturated counterparts.…”
Section: Redox-silent Tocopherol Derivatives: Modifications Of the Fumentioning
confidence: 96%
“…Although experience with mitomycin C revealed an acceptable safety profile [25,26], alternative antiproliferative agents with less cytotoxic and cell degenerative effects compared to mitomycin C would still be needed. In prior studies, vitamin E isoforms have revealed an antifibrotic potential [17][18][19]21]. Based on these findings, we evaluated the effects of different tocotrienol isoforms and concentrations on human Tenon's fibroblasts regarding inhibition of proliferation, migration, and collagen synthesis, revealing a significant antifibrotic effect for all tested isoforms.…”
Section: Discussionmentioning
confidence: 93%
“…Higher (and therefore eventually more effective) concentrations have not been tested. Based on prior studies [19][20][21] γ-und δ-isoforms of tocotrienol may even have a better antiproliferative effect than α-tocotrienol. Therefore, the aim of this study was to evaluate the tocotrienol isoform with the highest antifibrotic effect compared to mitomycin C in vitro.…”
Section: Introductionmentioning
confidence: 99%